Réseaux familiaux et institutionnels des religieuses : des alliés en justice ? Le cas des Visitandines de Rennes (xviie-xviiie siècles) - Aude Loriaud (Criminocorpus)
The unpublished correspondence exchanged between the Visitandines of Rennes, Bordeaux, Paris and Vannes (1641-1658, 1678-1683) is an exceptional source to shed light on nuns’judicial strategies. These letters are full of interest, not only to show their capability to rely on relational resources in provincial courts, but also to reveal the ability of a convent, recently established, to employ a judicial network including other convents of its order. Thus, the Visitandines of Bordeaux were able to win a trial in the parliament of Brittany thanks to the Visitandines of Rennes. We can sketch a complex network consisting of institutional, family and friendly links, and reveal informal gratuities to judicial officers. The judicial proceedings of the two monasteries of the Visitation of Rennes, in the 17th and 18th centuries, enables to check nuns’agency and highlight an important figure: the mother superior Claude Agnès Barrin.